The Importance of a Confirming Experiment in Pedagogical Work in Teaching the Science of Econometrics - Ravshanova Muhayyo Maxmanazarovna (Genius Publishing Group, 2022)
In this article, the researcher touched upon the process of conducting an experiment confirming pedagogical work in teaching the science of econometrics. In the article, the author also provided information about the types of pedagogical exposures.
Keywords: experiment; pedagogical-exponential; econometrics; pedagogical management